Black's law dictionary - Garner, Bryan A.; Black, Henry Campbell, 1860-1927. (St. Paul, MN : Thomson Reuters, 2014)
For more than a century, Black's Law Dictionary has been the gold standard for the language of law. This edition contains more than 50,000 terms, including more than 7,500 terms new to this edition. It also features expanded bibliographic coverage, definitions of more than 1,000 law-related abbreviations and acronyms, and reviewed and edited Latin maxims.
Preface to the Tenth edition -- Preface to the Ninth edition -- Preface to the Eighth edition -- Preface to the Seventh edition -- Guide to the dictionary -- List of abbreviations in definitions -- Dictionary: -- Appendixes: -- Table of legal abbreviations -- Legal maxims -- Declaration of independence -- Constitution of the United States -- Universal Declaration of Human Rights -- Members of the United States Supreme Court -- Federal circuits map -- British regnal years -- Bibliography of books cited.
Includes bibliographical references (pages 1995-2016).
Keywords: Law -- United States -- Dictionaries; Law -- Dictionaries; Dictionnaires; Droit; Law; Jurisprudence -- United States -- Dictionary; Jurisprudence -- United States -- Terminology; Legislation as Topic -- United States -- Dictionary; 2; United States; Dictionary; Terminology; Dictionaries; Dictionaries